2012
DOI: 10.1523/jneurosci.2250-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Notch Prosensory Effects in the Mammalian Cochlea Are Partially Mediated by Fgf20

Abstract: Hearing loss is becoming an increasingly prevalent problem affecting more than 250 million people worldwide. During development, fibroblast growth factors (FGFs) are required for inner ear development as well as hair cell formation in the mammalian cochlea and thus make attractive therapeutic candidates for the regeneration of sensory cells. Previous findings showed that Fgfr1 conditional knock out mice exhibited hair cell and support cell formation defects. Immunoblocking with Fgf20 antibody in vitro produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…We also found that Jag1b is required for fgf10a expression, suggesting Fgf10a may be a signal that mediates cell survival of posterior prosensory patches. In agreement with our finding, a previous study indicated that Notch functions upstream of Fgf20 and Notch-mediated regulation of prosensory formation in the cochlea occurs via Fgf20 (Munnamalai et al, 2012). In addition, Fgf10 expression was also reduced in the inner ear of RBPj CKO mice (Yamamoto et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…We also found that Jag1b is required for fgf10a expression, suggesting Fgf10a may be a signal that mediates cell survival of posterior prosensory patches. In agreement with our finding, a previous study indicated that Notch functions upstream of Fgf20 and Notch-mediated regulation of prosensory formation in the cochlea occurs via Fgf20 (Munnamalai et al, 2012). In addition, Fgf10 expression was also reduced in the inner ear of RBPj CKO mice (Yamamoto et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Instead, DAPT inhibited prosensory formation. Prosensory inhibition due to DAPT treatment occurs comparably early (E12.5) and typically requires a higher dose of DAPT (30 µM) (Munnamalai et al, 2012; as compared with Fig. 5E).…”
Section: Medial Compartment Expansion Is Partially Mediated By Notch mentioning
confidence: 82%
“…Second, conditional deletion of Jag1 leads to the downregulation of this prosensory marker, resulting in a malformed cochlear duct that contains few hair cells and supporting cells (Brooker et al, 2006;Kiernan et al, 2006). Third, cultured explants exposed to Notch inhibitors fail to form a prosensory domain (Munnamalai et al, 2012). Conversely, gain-of-function studies using virus-mediated overexpression of NICD in the chick cochlear duct (Daudet and Lewis, 2005) or transgenic approaches in the mouse inner ear (Hartman et al, 2010;Liu et al, 2012b;Pan et al, 2013) result in ectopic sensory patches composed of hair cells and supporting cells.…”
Section: Kip1mentioning
confidence: 99%
“…Two independent studies pinpointed FGF20 as the candidate ligand for FGFR1 in the cochlea, with both FGF20 and FGFR1 being required for the development of at least a subset of hair cells and supporting cells (Hayashi et al, 2008;Huh et al, 2012). The prosensory effect of FGF20 was further shown to act downstream of Notch signaling; FGF20 treatment rescues prosensory specification that is impeded by Notch inhibition (Munnamalai et al, 2012). Remarkably, deletion of Fgf20 did not lead to vestibular dysfunction, suggesting that the role of FGF20 in hair cell specification might be specific to the cochlea.…”
Section: Fgf Signalingmentioning
confidence: 99%
See 1 more Smart Citation